Empirical evaluation of RFID-based indoor localization with human body effect - Pathanawongthum, Nichapat; Cherntanomwong, Panarat (My University, 2009)
In this paper, the human body effect on indoor localization is evaluated based on experiments. Radio Frequency Identification (RFID) technology is used for this localization system. The location of a RFID reader is estimated based on the known locations of the RFID tags attached to the ceiling with 60 cm separation. Two cases of experiments are considered. For the first case, the RFID reader is attached to the camera tripod and the second case, it is attached to human body. Then, two simple location estimation methods are employed. To evaluate the effect of human body on the localization, the results of location estimation with and without human are compared. The experimental results illustrate that the human body affects the location estimation in some certain. However, the error of location estimation is still less than 50 cm which is applicable for some indoor applications. ©2009 IEEE.
Keywords: Human body; Indoor localization; RFID